Indigenous interpretation in parks and protected areas on Turtle Island: a scoping review - Lemelin, Raynald Harvey; Hurst, Chris E.; Grimwood, Bryan S. R. (Frontiers in Sustainable Tourism, 2024)
The interpretation of national, provincial, territorial, and state parks and heritage sites is a powerful social force that can foster or thwart respectful relationships between Indigenous and non-Indigenous peoples. By conducting a scoping review of relevant literature, this study aims to initiate conversations about how Indigenous interpretation is conceptualized and practiced in relation to national, provincial, territorial, and state parks and heritage sites on Turtle Island (i.e., North America). Findings indicate that while Indigenous interpretation is rarely explicitly defined, several themes are consistently used to illustrate what Indigenous interpretation entails or should entail. Themes include: i) responsibility and respect, ii) relationships, iii) place-based cultural identity and empowerment, iv) contested stories and histories, and v) storytelling. While these thematic dimensions do not represent a definitive definition of Indigenous interpretation, they do suggest potential features that may enhance understandings and applications of Indigenous interpretation in parks, protected areas, and heritage sites on Turtle Island. They also reaffirm the importance of interpretive encounters as a social force encouraging relationships across cultures.